2021
DOI: 10.1016/j.jcjp.2021.100013
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Autologous Chondrocyte Implantation (HD-ACI) in patients with bilateral knee chondral defects

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…6,7 Currently, the methods used to treat cartilage defects include surgeries contain microfractures, autologous osteochondral transplantation, and autologous chondrocyte implantation. [8][9][10] These treatments can improve some of the symptoms, but some adverse reactions are reported. 11,12 In recent years, tissue engineering (TE) has made considerable progress in obtaining functional articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Currently, the methods used to treat cartilage defects include surgeries contain microfractures, autologous osteochondral transplantation, and autologous chondrocyte implantation. [8][9][10] These treatments can improve some of the symptoms, but some adverse reactions are reported. 11,12 In recent years, tissue engineering (TE) has made considerable progress in obtaining functional articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…If patients' choice was to undergo one single surgery they only have to recover from one surgery while suffering the inconvenience of having both legs immobilized. 10 In that work we concluded that simultaneous treatment of chondral defects from both limbs with HD-ACI is a safe procedure with good results in terms of clinical outcome and quality of life. 10 Given the good results obtained in the knee we followed the same procedure with cartilage lesions in both ankles and 2 patients accepted to have just one surgery in which one ankle was operated after the other.…”
Section: Discussionmentioning
confidence: 87%
“…As described in a previous study conducted on patients with bilateral knee cartilage lesions, the main issue is to decide whether to operate both limbs in the same surgical act or in separate ones. 10 In this previous study, eight patients with bilateral knee chondral defects consecutively treated with HD-ACI, were included. We first explained the pros-and cons-of each option to patients and they decided whether they would like to undergo one or two surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations